If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(6z + -1) + 8(z + 4) = 0 Reorder the terms: -6(-1 + 6z) + 8(z + 4) = 0 (-1 * -6 + 6z * -6) + 8(z + 4) = 0 (6 + -36z) + 8(z + 4) = 0 Reorder the terms: 6 + -36z + 8(4 + z) = 0 6 + -36z + (4 * 8 + z * 8) = 0 6 + -36z + (32 + 8z) = 0 Reorder the terms: 6 + 32 + -36z + 8z = 0 Combine like terms: 6 + 32 = 38 38 + -36z + 8z = 0 Combine like terms: -36z + 8z = -28z 38 + -28z = 0 Solving 38 + -28z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + -28z = 0 + -38 Combine like terms: 38 + -38 = 0 0 + -28z = 0 + -38 -28z = 0 + -38 Combine like terms: 0 + -38 = -38 -28z = -38 Divide each side by '-28'. z = 1.357142857 Simplifying z = 1.357142857
| 0.2(x+100)+0.6x=36 | | 8(n-8)=-34-7n | | 12(2x-1)=9(2x+1)+9 | | q(2+3q)-q(5q-7)= | | 0.15x+0.05(4-x)=0.10(12) | | .25(.9x)=nx | | 4(s+3)-1=3x-5 | | 21/4x-1/2 | | -3(1-9z)-(-11z-11)= | | 3(-7-2x)+6(3x-7)=-51 | | 2x-6x+3x= | | 34=-2(2p+5)+5(1-7p) | | X=1.75+1.75X | | 3(t+7)-4=17 | | -4n-4(n-1)=12 | | 5=1+n-2 | | 5x^3+14x^2-3x=0 | | -(1-6x)-5=12 | | (a^4*-ac)+(c^3*d^2)= | | 5/7x15 | | 15x+25y=1400 | | c/5-c-1/10=9/10 | | 5X+7-2x=-11 | | 2y-10x=70 | | 17=3t+5 | | 5x-3y+2x+y= | | 6=3s-3 | | 3.12-d+2.1=1.910 | | (8+7i)-(-2+3i)= | | c-2.2+7.35=9.2 | | 2x+81=99 | | B-4.14=2.13-1.14 |